Molecular characterization of Fasciola hepatica in endemic regions of Colombia - Garcia-Corredor, Diego; Alvarado, Mateo; Pulido-Medellín, Martín; Muñoz, Marina; Cruz-Saavedra, Lissa; Hernández, Carolina; Giraldo, Julio Cesar; Vásquez-Arteaga, Luis R.; Morillo Coronado, Ana Cruz; Ramírez, Juan David (Frontiers in Veterinary Science, 2023)
Fasciola hepatica is a zoonotic trematode that affects a wide range of hosts, including cattle, sheep, and goats. The economic impact of the parasite on the cattle industry is significant, with high losses reported worldwide. While its impact on human health was previously underestimated, recent years have seen a rise in fascioliasis cases, leading to increased interest among researchers globally. To characterize the genetic diversity and intraspecific variation of this parasite in South America, specifically in Colombia, we collected 105 adult parasites from cattle bile ducts in seven Colombian departments (Antioquia, Boyacá, Santander, Cauca, Cundinamarca, Nariño, Norte de Santander, and Santander) to assess the parasite’s phenotypic analyses, genetic diversity, and population structure. A computer image analysis system (CIAS) was applied based on standardized morphological measurements. Liver-fluke size was studied by principal component analysis (PCA). DNA sequences were obtained for nuclear markers such as the 28S, β-tubulin 3, ITS1, ITS2, and the mitochondrial marker Cytochrome Oxidase I (COI). Multiple statistical tests were performed, and the parasite’s population structure was analyzed. Maximum Likelihood (ML) phylogenetic reconstructions were carried out using the sequences obtained herein and sequences available in GenBank. Morphological results revealed that all the obtained individuals matched F. hepatica’s morphology. There was no evidence of high genetic diversity, and the absence of genetic structure at the country-level was notable, possibly caused by a demographic expansion of this trematode in Colombia or the low resolution of the molecular markers employed. Future studies are still needed to unveil the genetic population structure of F. hepatica across the country.